The Implementation of Think-Pair-Share Technique to Increase Students’active Involvement in Their Speaking Ability - Ika Purnama Sari; Rizky Khairunnisa Sormin (Universitas Riau, 2022)
This research was conducted to increase students’active involvement in their speaking ability by using the Think-Pair-Share Technique. The researcher wanted to find out whether or not Think-Pair-Share Technique can increase the students speaking skill and to analyze the classroom situation when the Think-Pair-Share Technique is implemented in speaking class. This research used Classroom Action Research (CAR) and composed for two or more cycles then it observed and evaluated to identify all facts including the success and the failure of the action. It means that the action should be stopped or continued and revised to the next cycle based on the selected criteria of success. After the implementation of Think-Pair-Share Technique in every cycle, the students’ speaking score were getting better. It can be seen from the result of students averagescore Cycle 1 was 65.17 and Cycle 2 was 74.81. It can be concluded that Think-Pair-Share Technique canincrease students’active involvement in their speaking ability.